PENGARUH KOMUNIKASI, MOTIVASI, DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI LEMBAGA PENJAMINAN MUTU PENDIDIKAN - Alam, Syamsu (Katalogis, 2014)
The research aims to know and analyze simultaneous and partial effects of communication,Â motivation and job discipline on personnel performance at Education Quality Assurance Institution, Central Sulawesi Province. This study covers 95 personnel who have been determined using census method. To collect data, this study employ observation, questionnaire, documentation and interview. Analysis technique uses in this research is multiple linear regression to test relationship between dependent and independent variables. The results show that simultaneously and partially communication, motivation and job discipline perform positive and significant effects on personnel performance at Education Quality Assurance Institution, Central Sulawesi Province.